(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article presents a scientific analysis of the development of digital post-production technologies in Uzbekistan and their impact on the quality of film and media products. The research examines editing, color grading, and digital sound design processes based on practical observation, expert interviews, and technical analysis of completed media works. The findings show that digital post-production components increase production efficiency, enhance visual and audio quality, and strengthen studios’ ability to create more professional content in shorter time frames. Continuous technological upgrades are also reshaping the economic model of the media market and expanding the demand for high-quality content. At the same time, the study identifies certain limitations, such as a shortage of qualified specialists and uneven development of technical infrastructure. Overall, digital post-production technologies are emerging as a key strategic factor enhancing the competitiveness of Uzbekistan’s media industry.